2014
DOI: 10.1038/ncomms5365
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic hypervalent iodine(III)-mediated radiofluorination of non-activated and hindered aromatics

Abstract: Fluorine-18 (t ½ ¼ 109.7 min) is the most commonly used isotope to prepare radiopharmaceuticals for molecular imaging by positron emission tomography (PET). Nucleophilic aromatic substitution reactions of suitably activated (electron-deficient) aromatic substrates with no-carrier-added [ 18 F]fluoride ion are routinely carried out in the synthesis of radiotracers in high specific activities. Despite extensive efforts to develop a general 18 F-labelling technique for non-activated arenes there is an urgent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
195
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 40 publications
3
195
1
5
Order By: Relevance
“…A recent study by Coenen and coworkers demonstrated the satisfactory application of this method using Meldrum’s acid auxiliaries, but led to non-regiospecific labeling and formation of several byproducts (7). Concurrently, we explored the application of iodonium ylide precursors with barbituric acid and Meldrum’s acid auxiliaries for 18 F-labeling but also found yields to be sub-optimal (8). We discovered that spirocyclic iodonium(III) ylide precursors, in conjunction with systematic optimization of the reaction conditions, led to efficient, regiospecific, one-step radiosyntheses of non-activated aromatics with 18 F-fluoride (8).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Coenen and coworkers demonstrated the satisfactory application of this method using Meldrum’s acid auxiliaries, but led to non-regiospecific labeling and formation of several byproducts (7). Concurrently, we explored the application of iodonium ylide precursors with barbituric acid and Meldrum’s acid auxiliaries for 18 F-labeling but also found yields to be sub-optimal (8). We discovered that spirocyclic iodonium(III) ylide precursors, in conjunction with systematic optimization of the reaction conditions, led to efficient, regiospecific, one-step radiosyntheses of non-activated aromatics with 18 F-fluoride (8).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been devoted to the preparation and characterization of spiro compounds due to diverse industrial and biomedical applications in medicine [1][2][3], catalysis [4], 18F-radiolabeling [5] and optical material [6][7][8]. The asymmetric characteristic of the molecules, owing to the chiral spiro carbon, is one of the important criteria of the biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…7073, 75 The aryl iodide 12 could be oxidized in chloroform. 70 Without further purification, the resulted intermediate could couple the spirocyclic auxiliaries (SPIAd) 71 directly to afford the desired ylide precursor 17 . In specific, oxidant m CPBA (1.3 mmol, 77% max.…”
Section: Methodsmentioning
confidence: 99%